SARS-CoV-2 Delta VOC in Scotland: demographics, risk of hospital admission, and vaccine effectiveness - Sheikh, Aziz; McMenamin, Jim; Taylor, Bob; Robertson, Chris (The Lancet (British edition), 2021)
The Cox regression analysis for time to hospital admission found that S gene-positive cases were associated with an increased risk of COVID-19 hospital admission: hazard ratio (HR) 1·85 (95% CI 1·39–2·47) when compared to S gene-negative cases, after adjusting for age, sex, deprivation, temporal trend, and comorbidities. The corresponding hazard ratio for risk of hospital admission for S gene-positive cases was 0·38 (95% CI 0·24–0·58), with an interaction test p value of 0·19, suggesting that there was no evidence of a differential vaccine effect on hospital admissions among those first testing positive (appendix p 4). Considering the whole population cohort (rather than just hospital cases), the test-negative analysis to estimate vaccine effectiveness in preventing RT-PCR-confirmed SARS-CoV-2 infection showed that, compared to those unvaccinated, at least 14 days after the second dose, BNT162b2 (Pfizer–BioNTech vaccine) offered very good protection: 92% (95% CI 90–93) S gene-negative, 79% (75–82) S gene-positive.